1996
DOI: 10.1042/bj3200651
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C bound to the Golgi apparatus supports the formation of constitutive transport vesicles

Abstract: Constitutive secretion of heparan sulphate proteoglycans (HSPGs) was stimulated in human hepatoma HepG2 cells by phorbol 12-myristate 13-acetate (PMA) and inhibited by calphostin C, a specific inhibitor of protein kinase C (PKC). To delineate more closely the site of PKC action, the packaging in vitro of 35SO4-labelled HSPGs into transport vesicles was investigated. Formation of transport vesicles at the trans-Golgi network was stimulated by PMA and inhibited by calphostin C or Ro 31-8220 by using a post-nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…suggest that this function might involve syndapin II. To examine whether syndapins are crucial for this process and, specifically, whether interactions of the syndapin SH3 domain with dynamin II are required, we used an experimental system invented by Tooze and Huttner that allows the reconstitution, measurement and manipulation of the budding of vesicles from isolated Golgi membranes in vitro (Tooze and Huttner, 1992;Westermann et al, 1996;Dong et al, 2000b). The assay has been extensively characterized Dong et al, 2000b) and is based on the incubation of cell extracts with ATP, GTP, an ATP-regenerating system and the subsequent isolation of newly formed vesicles by differential Journal of Cell Science 119 (8) centrifugation.…”
Section: Journal Of Cell Science 119 (8)mentioning
confidence: 99%
“…suggest that this function might involve syndapin II. To examine whether syndapins are crucial for this process and, specifically, whether interactions of the syndapin SH3 domain with dynamin II are required, we used an experimental system invented by Tooze and Huttner that allows the reconstitution, measurement and manipulation of the budding of vesicles from isolated Golgi membranes in vitro (Tooze and Huttner, 1992;Westermann et al, 1996;Dong et al, 2000b). The assay has been extensively characterized Dong et al, 2000b) and is based on the incubation of cell extracts with ATP, GTP, an ATP-regenerating system and the subsequent isolation of newly formed vesicles by differential Journal of Cell Science 119 (8) centrifugation.…”
Section: Journal Of Cell Science 119 (8)mentioning
confidence: 99%
“…52 Moreover, recent studies showed that treatment of rat basophilic leukemia or HepG2 cells with the PKC inducer PMA stimulated the formation of transport vesicles at the TGN due to an increased binding of cPKCa to Golgi membranes associated with cPKCa-dependent phosphorylation of Golgi-associated proteins. [53][54][55] These processes were strongly inhibited in the presence of specific PKC inhibitors. 53,54 In consideration of our results and the literature data, we altogether conclude that PB-, TCPOBOP-or PMA-dependent activation of cPKC isoforms exerts distinct, cell compartmentspecific effects.…”
Section: Discussionmentioning
confidence: 97%
“…[53][54][55] These processes were strongly inhibited in the presence of specific PKC inhibitors. 53,54 In consideration of our results and the literature data, we altogether conclude that PB-, TCPOBOP-or PMA-dependent activation of cPKC isoforms exerts distinct, cell compartmentspecific effects. At the Golgi apparatus, cPKC isoforms stimulate the generation of Rfc1 transport vesicles associated with an increased targeting of intracellular Rfc1 molecules from the Golgi compartment to the basolateral membrane.…”
Section: Discussionmentioning
confidence: 97%
“…This could be a mechanism whereby activated PKC⑀ could regulate Golgi function. In addition, study of secretion of heparan sulfate proteoglycans from HepG2 cells showed that membrane-bound PKC supported vesicle formation with PKC␣ and PKC attaching to highly purified Golgi membranes (22). We have previously demonstrated that PKC␤ and PKC␦ associate with the microtubule cytoskeleton/MTOC in locomotory T cells, while others have shown that modulation of PKC activity can prevent reorientation of the MTOC in cytotoxic T cells (9,23).…”
Section: Resultsmentioning
confidence: 99%